1999
DOI: 10.1097/00005768-199903000-00003
|View full text |Cite
|
Sign up to set email alerts
|

The benefits of wearing a compression sleeve after ACL reconstruction

Abstract: It was concluded that a compression sleeve improved the total integration of the balance control system and muscle coordination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
1
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 22 publications
3
62
1
2
Order By: Relevance
“…These findings were consistent with previous research by Birmingham that reported knee brace had no significant effect on balance control in challenging balance tasks (10). The more balance demanding tasks need considerable motor activity (16).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These findings were consistent with previous research by Birmingham that reported knee brace had no significant effect on balance control in challenging balance tasks (10). The more balance demanding tasks need considerable motor activity (16).…”
Section: Discussionsupporting
confidence: 92%
“…Birmingham et al reported no effect of brace on mediolateral COP sway in subjects with ACLreconstruction (9). Kuster et al (10) found that wearing knee bandage had no significant effect on the one legged stance balance control mediolateral sway amplitude.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study by Kuster et al, 36 patients who had had ACL (anterior cruciate ligament) reconstruction performed a single-leg drop jump test from a 10 cm high platform and landed 20 cm in front of the platform. The dynamic balance in the single-leg standing position was evaluated for 25 seconds after landing 36) . Franz et al measured the COP speed, COP sway, and ground reaction force of 25 healthy subjects who jumped from a 30 cm high step and landed on a force plate in front of them 37) .…”
Section: Cop Total Track Lengthmentioning
confidence: 99%